2018
DOI: 10.1371/journal.pone.0199398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic significance of EBER positivity in diffuse large B-cell lymphoma: A meta-analysis

Abstract: Recent studies show that Epstein-Barr virus (EBV) positivity might be related to adverse prognosis in patients with diffuse large B-cell lymphoma (DLBCL), but the results are still inconclusive. We conducted this meta-analysis to define the clinical value of EBV infection in DLBCL. All potential articles in PubMed, Web of Science, Medline, and Embase were retrieved. Using the random-effects or fixed-effect model, pooled hazard ratios (HRs) or relative risk (RR) with 95% confidence intervals (CIs) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
(94 reference statements)
3
26
0
2
Order By: Relevance
“…Unlike a recent report by Gao et al . we found our cohort of EBV + DLBCL (NOS) not be enriched for presence of B symptoms, which were a strong prognosticator in terms of both PFS and OS (Gao et al , ). This may well be attributed to the fact that prior investigations were not restricted to a specific subtype of NHL.…”
Section: Discussionmentioning
confidence: 77%
“…Unlike a recent report by Gao et al . we found our cohort of EBV + DLBCL (NOS) not be enriched for presence of B symptoms, which were a strong prognosticator in terms of both PFS and OS (Gao et al , ). This may well be attributed to the fact that prior investigations were not restricted to a specific subtype of NHL.…”
Section: Discussionmentioning
confidence: 77%
“…Lymphoma, the most common non-epithelial malignancy of the head and neck region, can be classified into two types, Hodgkin’s lymphoma (HL) and non-Hodgkin’s lymphoma (NHL) [1]. Among them, primary nasopharyngeal (NP) lymphoma is a very rare tumor, with only limited studies found in the literatures [2,3,4,5,6,7,8,9,10]. Waldeyer-Hartz firstly described the lymphoid tissues within the nasopharynx, oropharyngeal wall, base of the tongue, palatine tonsils, and soft palate, known today as Waldeyer’s ring (WR) [7].…”
Section: Introductionmentioning
confidence: 99%
“…EBV-associated viral proteins were found to play important roles in the genesis of lymphomas through several mechanisms [10,14,15,16,17]. The expression of EBV-encoded small RNAs (EBER) is common in NKTCL, while EBER positivity is still controversial in DLBCL [10,18,19,20,21,22]. There are studies reporting that EBER-positive patients have a poorer prognosis than EBER-negative patients [10,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Epstein-Barr encoding region (EBER) in-situ hybridisation was positive in neoplastic cells, which has been associated with a more aggressive clinical course and worse overall prognosis in diffuse large B-cell lymphoma Figure 1. 2 Amplification of the immunoglobulin heavy chain (IgH) gene by polymerase chain reaction (PCR) confirmed B-cell clonality with FR3 primers. This is indicative of a proliferation of genetically identical cells.…”
Section: Clinical Historymentioning
confidence: 99%